Amniotic fluid INSL3 measured during the critical time window in human pregnancy relates to cryptorchidism, hypospadias and phthalate load: a large case-control study - Anand-Ivell, Ravinder; Cohen, Arieh; Norgaard-Pedersen, Bent; Joenssen, Bo; Bonde, Jens-Peter; Hougaard, David M.; Lindh, Christian; Toft, Gunnar; Lindhard, Morten; Ivell, Richard (Frontiers Research Foundation, 2018)
The period of the first to second trimester transition in human pregnancy represents a sensitive window for fetal organogenesis, particularly in regard to the development of the male reproductive system. This is a time of relative analytical inaccessibility. We have used a large national biobank of amniotic fluid samples collected at routine amniocentesis to determine the impacts of exogenous endocrine disruptor load on specific fetal biomarkers at this critical time. While adrenal and testicular steroids are highly correlated, they are also mostly positively influenced by increasing phthalate load, represented by the metabolites 7cx-MMeHP and 5cx-MEPP, by PFOS exposure, and by smoking, suggesting an adrenal stress response. In contrast, the testis specific biomarkers INSL3 and androstenedione are negatively impacted by the phthalate endocrine disruptors. Using a case-control design, we show that cryptorchidism and hypospadias are both significantly associated with increased amniotic concentration of INSL3 during gestational weeks 13 to 16, and some, though not all steroid biomarkers. Cases are also linked to a specifically increased variance in the Leydig cell biomarker INSL3 compared to controls, an effect exacerbated by maternal smoking. No influence of phthalate metabolites or PFOS was evident on the distribution of cases and controls. Considering that several animal and human studies have shown a negative impact of phthalate load on fetal and cord blood INSL3, respectively, the present results suggest that such endocrine disruptors may rather be altering the relative dynamics of testicular development and consequent hormone production, leading to a desynchronization of tissue organization during fetal development. Being born small for gestational age appears not to impact on the testicular biomarker INSL3 in second trimester amniotic fluid.